Sales of arabica coffee brand "seplawan" based on digital marketing at CV Gunungkelir Cipta Mandiri, Purworejo Regency, Central Java - Utami, Dyah Panuntun; Widyantono, Didik; Diantama, Dimas Wahyu (Jurnal Agrotek Ummat, 2023)
Purworejo is one of the Arabica coffee producers with a plantation area of 529 hectares and production reaching 171 tons. This potential encourages the emergence of MSMEs that process coffee and one of them is Seplawan coffee. This study aims to determine the impact of implementing digital marketing on sales of Arabica coffee with the Seplawan brand, and to find out the differences in sales of Arabica coffee before and after implementing digital marketing. The research method uses case studies, and the determination of research locations is by purposive sampling. Data analysis used descriptive analysis and different test (t test) with a significance level of 95%. The results showed that the use of digital marketing had an impact on increasing sales of Seplawan coffee. Significant differences in coffee sales at the stage before and after being established in using digital marketing are found in sales of coffee sizes of 100 grams, 500 grams and 1000 grams.